Penerapan Metode Demonstrasi Berbasis Lingkungan Untuk Meningkatkan Hasil Belajar IPA Pada Siswa Kelas VI Satuan Pendidikan SD Negeri 3 Seraya Timur - I Ketut Tirtayasa (Jayapangus Press, 2021)
This research is motivated by the low learning outcomes of grade VI students of SD Negeri 3 Seraya Timur in learning the content of science subjects. This is thought to be caused by several factors, the learning method used is still monotonous and less varied, namely only using the lecture method and the lack of learning support facilities so that learning is less effective. This classroom action research was carried out in two cycles with the aim of improving science learning outcomes. The subjects of this study were sixth grade students of SD Negeri 3 Seraya Timur with a total of 18 students consisting of 8 female students and 10 male students. Data were collected using the test method. The results of the study show that the application of environmental-based demonstration methods in science learning can improve student learning outcomes. Based on the initial reflection analysis, the average learning outcome reaches 60.00 and the percentage of learning outcomes reaches 60.00% in the poor category. While in the first cycle, the average learning outcomes reached 73.61 and the percentage of learning outcomes reached 73.61%. This percentage shows on a good scale. While in the second cycle, the average learning outcomes in the second cycle reached 82.78 and the percentage of learning outcomes reached 82.78%. This percentage shows in the very good category. From the explanation above, this research has been able to answer the problem formulation as well as being able to solve the problem of the low science learning outcomes of sixth grade students of SD Negeri 3 Seraya Timur. This is also supported by an increase in student learning activity towards the learning carried out, in other words, the classroom action research has been successful.